Barbar - König - Tyrann Das Bild Theoderichs des Großen in der Überlieferung des 5. bis 9. Jahrhunderts - Goltz, Andreas (Millennium-Studien / Millennium Studies, 2009)
Theodoric the Great is one of the most fascinating characters among the rulers from the time of the migrations of the Germanic peoples. Like no other Germanic king, this East Goth polarised the world of his time and made an impression on posterity. Opinions on him range from glorifying him as the ideal ruler to condemning him as a tyrant and heretical persecutor. Andreas Goltz examines the many-faceted image of Theoderic in the early centuries after his death (5th𔃇th centuries), analyzes the reasons behind the different views of him, and thus helps us to understand Theoderic, his age, and the history of his reception and influence.